Comparative Evaluation of Shear Bond Strength of Glass Ionomer Cement, Resin-Modified Glass Ionomer Cement and Alkasite Restorative Material to Human Dentin: An In-Vitro Study (Academia Journal of Medicine, 2026)
Background: Durable adhesion between restorative materials and dentin is essential for the longevity and clinical success of restorations. Conventional glass ionomer cement (GIC), resin-modified glass ionomer cement (RMGIC), and alkasite restorative materials are widely used because of their fluoride release, chemical bonding potential, and simplified clinical application; however, their comparative bonding performance remains inconclusive. Aim: To compare the shear bond strength (SBS) of conventional GIC, RMGIC, and alkasite restorative material to human dentin. Materials and Methods: Thirty extracted human premolars were sectioned to expose flat mid-coronal dentin surfaces and randomly allocated into three groups (n = 10): Group I—conventional GIC, Group II—RMGIC, and Group III—alkasite restorative material. Restorations were placed according to manufacturers’ instructions using a standardized cylindrical mold. After storage in distilled water at 37 °C for 24 hours, specimens were subjected to shear bond strength testing using a universal testing machine at a cross-head speed of 1 mm/min. SBS values were calculated in megapascals (MPa) and statistically analyzed using one-way analysis of variance followed by Tukey’s post-hoc test (α = 0.05). Results: Alkasite restorative material demonstrated the highest mean shear bond strength (14.06 ± 1.87 MPa), followed by RMGIC (11.52 ± 1.74 MPa) and conventional GIC (8.94 ± 1.58 MPa). The differences among the three groups were statistically significant (p < 0.001). Conclusion: Within the limitations of this in-vitro study, alkasite restorative material exhibited superior bonding to dentin compared with both types of glass ionomer cements. Conventional GIC showed the lowest shear bond strength.
Keywords: Shear bond strength; glass ionomer cement; resin-modified glass ionomer cement; alkasite; dentin adhesion; restorative dentistry